A Latin lexicon : an illustrated compendium of Latin words and English derivatives - Mackenzie, Caroline K. (Archaeopress Publishing Ltd, 2020)
This charming, illustrated compendium of Latin words and English derivatives, includes over 365 words required for Latin GCSE. Key notes on grammar, translations and playful and memorable derivatives accompany each Latin entry, and a glossary of Latin in common usage make this essential for all learners of Latin as well as cruciverbalists.